The association between food environment, diet quality and malnutrition in low‐ and middle‐income adult populations across the rural—Urban gradient in Vietnam - Vuong, Vy Thao; Fiorella, Kathryn J.; Jones, Andrew D.; Thi Trinh, Huong; Khoury, Colin K.; Huynh, Tuyen; Hoang, Ky The; Nguyen, Kien Tri (Wiley, 2023)
Background: Economic reforms and trade liberalisation in Vaietnm have transformed the food environment, influencing dietary patterns and malnutrition status. The present study focuses on the relationship between food environments (proximity and density of food outlets) and malnutrition (underweight, overweight, obesity) through diet quality in adult populations across urban, periurban and rural areas of Vietnam.